A study of peripheral input to and its control by post-ganglionic neurones of the inferior mesenteric ganglion. - Szurszewski, J H (1976)
1. Intracellular recordings were made, in vitro, from neurones of guinea-pig inferior mesenteric ganglia (IMG) attached, via the lumbar colonic nerves, to segments of distal colon. 2. 'Spontaneous' synaptic input from colonic afferent fibres was observed in 79% of the neurones tested. In any given preparation, the level and pattern of this synaptic input to different neurones varied considerably. 3. Superfusion of colonic segments with drugs (papaverine, isoprenaline, and adenosine triphosphate) which reduce colonic motility decreased colonic afferent input to IMG neurones. 4. Superfusion of colonic segments with acetylcholine or stimulation of pelvic nerves, both of which increase colonic motility, increased colonic afferent input to IMG neurones. 5. Superfusion of colonic segments with either atropine or tubocurarine reduced the level of 'spontaneous', colonic afferent input. However, distension of these relaxed segments increased the colonic afferent input. 6. Repetitive stimulation of preganglionic inputs to the IMG inhibited afferent input from drug relaxed segments of colon that were moderately distended by the injection of air into the lumen. Superfusion of the colon with phentolamine blocked this inhibition. 7. The results of this study suggest that IMG neurones receive afferent input from mechanoreceptors located in the distal colon and that the mechanosensitivity of this afferent pathway is in part controlled by efferent noradrenergic neurones of the IMG. The IMG-colon neural circuitry can therefore be considered to form a feed-back control system which participates in the regulation of colonic motility.